Técnica de macacos planos na avaliação de estruturas de alvenaria com blocos vazados de concreto - Soriani, Mateus de Oliveira (Universidade Federal de São Carlos, 2016)
The present study delas with nondestructive evaluation of modern masonry built with hollow concrete blocks, through the flatjack technique. The technique is already used to evaluate masonry structures with solid bricks and stones and it is considered as efficient to obtain in situ mechanical properties, without any permanent damages. The tests in solid unit masonry using flatjack is included in international standards and recommendations as: ASTM C 1196 e 1197-09 e RILEM MDT.D.4 e MDT.D.5-04. The current standards and the practical applications deal with masonry with brick or stones elements only. Nondestructive evaluation in modern hollow block masonry is demanded and the flatjack can be used in these cases. However, the current available jack can be used only on solid units, due to its geometrical limitations. Therefore, this research proposes to adapt the flatjack technique for nondestructive evaluation in modern masonry built with hollow concrete blocks. The analyzed test is the deformability one, which the modulus of elasticity and an estimative of the compressive strength is wanted. In this research, a new flatjack equipment was developed to allow its application on hollow blocks and it was tested in modern masonry samples. The new equipment was successfully developed and it was used in flatjack tests on hollow concrete block masonry. As main results, masonry properties obtained from the flatjack technique was close to the expected ones, indicating the great potentiality of the technique for hollow blocks also.
Keywords: Macacos planos; Teste de deformabilidade; Avaliação não destrutiva; Blocos vazados de concreto; Flatjack; Deformability test; Nondestructive evaluation; Hollow concrete blocks; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS